Does prior coronary angioplasty affect outcomes of surgical coronary revascularization? Insights from the STICH trial. (15th September 2019) - Nicolau, Jose C.; Stevens, Susanna R.; Al-Khalidi, Hussein R.; Jatene, Fabio B.; Furtado, Remo H.M.; Dallan, Luis A.O.; Lisboa, Luiz A.F.; Desvigne-Nickens, Patrice; Haddad, Haissam; Jolicoeur, E. Marc; Petrie, Mark C.; Doenst, Torsten; et al.
Abstract: Background: The STICH trial showed superiority of coronary artery bypass plus medical treatment (CABG) over medical treatment alone (MED) in patients with left ventricular ejection fraction (LVEF) ≤35%. In previous publications, percutaneous coronary intervention (PCI) prior to CABG was associated with worse prognosis. Objectives: The main purpose of this study was to analyse if prior PCI influenced outcomes in STICH. Methods and results: Patients in the STICH trial (n = 1212), followed for a median time of 9.8 years, were included in the present analyses. In the total population, 156 had a prior PCI (74 and 82, respectively, in the MED and CABG groups). In those with vs. without prior PCI, the adjusted hazard-ratios (aHRs) were 0.92 (95% CI = 0.74–1.15) for all-cause mortality, 0.85 (95% CI = 0.64–1.11) for CV mortality, and 1.43 (95% CI = 1.15–1.77) for CV hospitalization. In the group randomized to CABG without prior PCI, the aHRs were 0.82 (95% CI = 0.70–0.95) for all-cause mortality, 0.75 (95% CI = 0.62–0.90) for CV mortality and 0.67 (95% CI = 0.56–0.80) for CV hospitalization. In the group randomized to CABG with prior PCI, the aHRs were 0.76 (95% CI = 0.50–1.15) for all-cause mortality, 0.81 (95% CI = 0.49–1.36) for CV mortality and 0.61 (95% CI = 0.41–0.90) for CV hospitalization. There was no evidence of interaction between randomized treatment and prior PCI for any endpoint (all adjusted p > 0.05). Conclusion: In the STICH trial, prior PCI did not affect the outcomes of patients whether they were treated medically or surgically, and the superiority of CABG over MED remained unchanged regardless of prior PCI. Clinical trial registration: Clinicaltrials.gov ; Identifier:NCT00023595 Highlights: Prior reports suggested an association of prior PCI with worse outcomes after CABG. Patients with severe LV dysfunction were under-represented in those studies. STICH trial demonstrated survival benefit with CABG in severe LV dysfunction. This benefit was consistent regardless of the presence of prior PCI. Prior PCI should not contra-indicate CABG in patients with LV dysfunction.